Physiologically based pharmacokinetic model of renally cleared antibacterial drugs in Chinese renal impairment patients. (12th January 2021) - Cui, Cheng; Li, Xiaobei; Liang, Hao; Hou, Zhe; Tu, Siqi; Dong, Zhongqi; Yao, Xueting; Zhang, Miao; Zhang, Xuan; Li, Haiyan; Zuo, Xiaocong; Liu, Dongyang
Abstract: To preliminarily develop physiologically based population models for Chinese renal impairment patients and to evaluate the prediction performance of new population models by renally cleared antibacterial drugs. First, demographic data and physiological parameters of Chinese renal impairment patients were collected, and then the coefficients of the relative demographic and physiological equation were recalibrated to construct the new population models. Second, drug‐independent parameters of ceftazidime, cefodizime, vancomycin, and cefuroxime were collected and verified by Chinese healthy volunteers, Caucasian healthy volunteers, and Caucasian renal impairment population models built in Simcyp. Finally, the newly developed population models were applied to predict the plasma concentration of four antibacterial drugs in Chinese renal impairment patients. The new physiologically based pharmacokinetic (PBPK) population models can predict the main pharmacokinetic parameters, including area under the plasma concentration–time curve extrapolated to infinity (AUCinf ), renal clearance (CLr ), and peak concentration ( C max ), of ceftazidime, cefodizime, vancomycin, and cefuroxime following intravenous administrations with less than twofold error in mild, moderate, and severe Chinese renal impairment patients. The accuracy and precision of the predictions were improved compared with the Chinese healthy volunteers and Caucasian renal impairment population models. The PBPK population models were preliminarily developed and the first‐step validation results of four antibacterial drugs following intravenous administration showed acceptable accuracy and precision. The population models still need more systematic validation by using more drugs and scenarios in future studies to support their applications on dosage recommendation for Chinese renal impairment patients. Abstract : The PBPK population models of Chinese renal impaired patients were preliminarily developed by employing demographic and physiological parameters of Chinese patients and results of first steps towards verification by four antibacterial drugs following IV administration showed acceptable accuracy and precision in Chinese patients with mild, moderate, and severe renal impairment.